Classification of lithic artefacts from the British Late Glacial and Holocene periods - Ballin, Torben Bjarke, (Archaeopress Archaeology, 2021)
This volume offers a system for the hierarchical classification of British lithic artefacts from the Late Glacial and Holocene periods, and it is hoped that it may find use as a guide book for, for example, archaeology students, museum staff, non-specialist archaeologists, local archaeology groups and lay enthusiasts.